Left by the West? Academic Discourse on Corruption for a Better Social Resilience - Pernica, Bohuslav; Pikhart, Marcel (Emerging Science Journal, 2021)
The paper deals with the topic of corruption that has been understood as a global social problem since the 1990s. Its theoretical background is rooted in the theory of social constructivism. Social constructivism highlights the social strategy in which increased social discourse about a particular topic implies and reflects a growing interest of the society in the topic to arouse a robust awareness of the issue as a social problem. It analyses academic journals and conference paper proceedings that appear in a well-known database of academic journals and texts, namely in Web of Science. The research follows PRISMA methodology and it was conducted as an analysis of the terms and collocations that are connected to the issue of corruption with the aim to identify relevant research papers which have appeared in Web of Science since 1995. The idea behind this analysis was not only to identify the journal papers and papers published as conference proceedings but to compare the results geographically with well-known officially acknowledged state and government data dealing with the issue of corruption, and then to look for connections between these two areas, i.e. academic and governmental data. The results show significant differences between post-communist countries versus the so-called West regarding how they present information about corruption in their academic discourse. Despite the fact that the West supports the East in its fight with corruption economically, it is not reflected sufficiently and adequately in the relevant academic discourse. This paper suggests that societal resilience against corruption can dramatically be supported by enhanced academic discourse about the topic that is still not sufficient.Â Doi: 10.28991/esj-2021-01266 Full Text: PDF